CHANGE IN VISUAL FUNCTION IN PARKINSON'S DISEASE. Issue 12 (15th November 2016) - Weil, Rimona S; Pappa, Katerina; Burn, Hannah; Pavisic, Ivanna; Schwarzkopf, Sam; Warren, Jason; Morris, Huw
Abstract : Aim: To measure changes in visuo-perceptual processing in patients with Parkinson's disease without dementia. Methods: Images of cats and dogs that had been skewed by varying amounts were shown to patients with idiopathic Parkinson's disease (defined by QSBB criteria) (n=16) and healthy controls (n=11). Mean disease duration was 4 years (Standard deviation 3 years). Average L-DOPA equivalent dose was 554 mg (SD 487 mg). On each trial, participants were asked to identify the presented animal to generate psychophysical curves of skew against correctness and determine the threshold for identifying the correct animal. Visual acuity, UPDRS-scores and neuropsychology performance was measured for each participant. Results: Patients with Parkinson's disease, but without dementia, showed impaired ability to identify images that had been skewed, compared with healthy controls. The threshold for detection in patients was 61.2 degrees (SD 7.1 degrees), compared with 67.9 degrees (SD 2.1 degrees) in healthy participants, W=143, p=0.0056. The groups did not differ in visual acuity or neuropsychological performance. Conclusions: We show subtle but definite impairment of complex visual processing in the initial phases of Parkinson's disease in patients without overt cognitive impairment. This work has important implications for understanding the diagnosis, biology and progression of Parkinson's disease.